Integrasi Konsep Self-Regulated Learning dalam Perspektif Mujahadah an-nafs: Kritik Filosofis terhadap Krisis Etika Akademik di Era Kecerdasan Buatan (AI) - Aqimnad Dinana, Retno; Fahmi, Muhammad; Dewi Sholehah, Sukma; Tasya Putri Rohmadani, An’nas (IAIN Kendari, 2025)
The high use of generative Artificial Intelligence (AI) (95% in Indonesia) has triggered an academic integrity crisis and exacerbated the ethical deficit in the conventional pragmatic-focused Self-Regulated Learning (SRL) framework. Technical solutions such as plagiarism detectors fail to address the root of the problem, namely weak spiritual self-control. To address the urgent need for a morality regulator, this study uses the Qualitative Conceptual-Philosophical Analysis method with an in-depth literature review. This method is used to integrate the concept of the Zimmerman cycle of SRL with the Islamic perspective of Mujahadah an-Nafs (spiritual self-control). The main finding is a model mapping three spiritual pillars into the SRL cycle: Niyyah (intention) as a transcendental moral filter in the Forethought phase; Riyāḍah (training/discipline) as an action engine that counters immoral temptations (including AI plagiarism) in the Performance phase; and Muhasabah (self-evaluation) as a mirror of critical accountability in the Self-Reflection phase. In conclusion, this integration model serves as an internal three-layer anti-plagiarism strategy. The implication is the expansion of SRL's function from mere cognitive management to a character-building process (Tazkiyatun Nafs), which ensures honest and integrated academic output in the AI ​​era.